2001
DOI: 10.1002/1521-4036(200102)43:1<5::aid-bimj5>3.0.co;2-6
|View full text |Cite
|
Sign up to set email alerts
|

The Binary Regression Quantile Plot: Assessing the Importance of Predictors in Binary Regression Visually

Abstract: We present a graphical measure of assessing the explanatory power of regression models with a binary response. The binary regression quantile plot and an area defined by it are used for the visual comparison and ordering of nested binary response regression models. The plot shows how well various models explain the data. Two data sets are analyzed and the area representing the fit of a model is shown to agree with the usual likelihood ratio test.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
58
0
1

Year Published

2006
2006
2017
2017

Publication Types

Select...
4
2
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 43 publications
(60 citation statements)
references
References 10 publications
(8 reference statements)
1
58
0
1
Order By: Relevance
“…Therefore, the AARD can also be interpreted as a Kolmogorov-Smirnov distance between the case and control risk distributions. Finally, Huang and Pepe [10] and Gu and Pepe [7] showed that the standardized total gain statistic proposed by Bura and Gastwirth [2] as a measure of predictive capacity of a model risk(X), sT G = |risk(X) − ρ|dF (X)/2ρ(1 − ρ) is equal to the AARD.…”
Section: Measures Independent Of Risk Thresholdsmentioning
confidence: 99%
“…Therefore, the AARD can also be interpreted as a Kolmogorov-Smirnov distance between the case and control risk distributions. Finally, Huang and Pepe [10] and Gu and Pepe [7] showed that the standardized total gain statistic proposed by Bura and Gastwirth [2] as a measure of predictive capacity of a model risk(X), sT G = |risk(X) − ρ|dF (X)/2ρ(1 − ρ) is equal to the AARD.…”
Section: Measures Independent Of Risk Thresholdsmentioning
confidence: 99%
“…Total gain, proposed by Bura and Gastwirth (2001) is defined as , marker assigning risk(Y ) = ρ to all subjects. TG is appealing because it can be visualized directly from the predictiveness curve.…”
Section: Total Gainmentioning
confidence: 99%
“…Bura and Gastwirth (2001) used the risk quantiles, R(ν), to assess predictors in binary regression models. They proposed a summary index which they called the total gain.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The eAppendix relates MRS to many statistics, including discretized versions of statistics used 129 for continuous biomarkers [18][19][20][21][22] For a perfect test (PPV=1 and cNPV=0), the equation for MRS (1) reveals that the 156 maximum MRS is 50%, which occurs when disease prevalence and test positivity are both 50%. 157…”
Section: And the Area 61mentioning
confidence: 99%